1981
DOI: 10.1126/science.6259737
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal M Cells: A Pathway for Entry of Reovirus into the Host

Abstract: Thirty minutes after inoculation of reovirus type 1 into the intestinal lumen of the mouse, viruses were found adhering to the surface of intestinal M cells but not other epithelial cells. Within 1 hour, viruses were seen in the M cell cytoplasm and were associated with mononuclear cells in the intercellular space adjacent to the M cell. These findings suggest that M cells are the site where reovirus penetrates the intestinal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
231
0
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(234 citation statements)
references
References 14 publications
1
231
0
2
Order By: Relevance
“…M cells in the FAE provide an entry site for pathogens, such as S. typhimurium, Mycobacterium bovis, Shigella flexneri, Y. enterocolitica and retroviruses (4,(38)(39)(40). It is well known that the invasion genes of the Salmonella pathogenicity island (SPI1) are necessary for the entry of S. typhimurium into FAE-M cells and epithelial cells (38,41).…”
Section: Discussionmentioning
confidence: 99%
“…M cells in the FAE provide an entry site for pathogens, such as S. typhimurium, Mycobacterium bovis, Shigella flexneri, Y. enterocolitica and retroviruses (4,(38)(39)(40). It is well known that the invasion genes of the Salmonella pathogenicity island (SPI1) are necessary for the entry of S. typhimurium into FAE-M cells and epithelial cells (38,41).…”
Section: Discussionmentioning
confidence: 99%
“…M cells form tight junctions between abutting columnar cells, and are also reported to serve as a barrier between lymphoid cells and the luminal space to keep them in a certain proximity. Specific functions reported include the-uptake of horseradish peroxidase by mouse M cells within 5 min after its injection (6), the entry of Reovirus into the mouse tissue through the intestinal M cell (9), and the specific adherence of Escherichia coli strain RDEC-I to rabbit M cells (2,3). The authors of these reports suggested the ability of M cells to transport antigens to the enfolded lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium overlying the dome surface contains a number of a special type of cell, termed the M cell (OWEN and JONES, 1974), and differs from that of the surrounding villi. These M cells are believed to play an important role in the transportation of intraluminal antigens to the underlying lymphoid tissue (BOCKMAN and COOPER, 1973;OWEN, 1977;WOLF et al, 1981). Peyer's patches are attracting greater recognition as the major component of the gut-associated lymphoid tissue (GALT) which has a significant role not only in the local defense system but also in the systemic immune systmem (see review by KAGNOFF, 1987).…”
Section: Lymphoid Folliclesmentioning
confidence: 99%